ANALISIS PROFITABILITAS PADA PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dianita Savitri Anggraeni; Muhadjir Anwar (REVITALISASI : Jurnal Ilmu Manajemen, 2021)
Profitability is one of the goals in a company. Profitability describes the ability of a company to optimize its assets to generate profits. The goals of this study are to determine: (1) The impact of capital structure on profitability in mining sector companies on the Indonesia Stock Exchange for the 2017-2019 period. (2) The influence of capital structure which is moderated by company size on the profitability of Mining Sector Companies on the Indonesia Stock Exchange for the 2017- 2019 period. There are 37 were mining sector companies on the Indonesia Stock Exchange for the 2017-2019 period, where a sample was taken using a method of purposive sampling with certain criteria according to the research needs. The data used in this study is the secondary data in the form of financial reports published during the period specified in the study. This study used moderated regression analysis. The results showed that: (1) capital structure has a significant negative impact on profitability. (2) the size of a firm can moderate or strengthen the significant negative impact of capital structure on profitability.